African Librarians and the Future of Learning: Reflections from the 5thAfLIA Conference and 7th African Library Summit in Accra, Ghana - Igbinovia, Magnus Osahon; Okuonghae, Omorodion (Folia Toruniensia, 2023)
Innovations in the 21st century have reshaped learning among people of different age, educational qualification, race, gender and geographical location. As a lifelong behaviour, it is predicted that the future of learning will transcend the conventional learning pattern and walls of the classroom with the introduction of open practices (such as the open educational resources) and the decolonization of educational content for both formal and informal learning. This discussion and many more characterized the 5thAfLIA conference and 7th African Library Summit in Accra, Ghana, as Librarians in Africa gathered to discuss the future of learning, libraries and sustainable development in Africa. The conference provided opportunity for Librarians in Africa to re-think their place in the future of learning and help achieve sustainable development. This paper, therefore, highlights the key activities and issues discussed during the 5th AfLIA Conference and 7th African Library Summit held in Accra, Ghana, from 22nd to 26th May, 2023.